SOBRE A OCORRÃŠNCIA DE UM GEOMETRÃDEO EM ð˜—ð˜ªð˜¯ð˜¶ð˜´ ð˜°ð˜°ð˜¤ð˜¢ð˜³ð˜±ð˜¢ SCHIEDE - Berti Filho, Evoneo (REVISTA DE AGRICULTURA, 2020)
SOBRE A OCORRÃŠNCIA DE UM GEOMETRÃDEO EM ð˜—ð˜ªð˜¯ð˜¶ð˜´ ð˜°ð˜°ð˜¤ð˜¢ð˜³ð˜±ð˜¢ SCHIEDE